Quantitative Assessment of Eosinophils in Dermatomyositis Skin Biopsies With Correlation of Eosinophils to Pruritus and Other Clinical Features. (April 2021) - Khanna, Urmi; Vaughan, Heidi; North, Jeffrey; Haemel, Anna
Abstract : Abstract: The objective of this retrospective study was to analyze dermatomyositis skin biopsies for the presence of eosinophils and correlate this finding with other histopathologic and clinical characteristics. Cases of dermatomyositis evaluated in a single dermatologist's adult autoimmunity practice over a 2.5-year period were identified via ICD-10 diagnosis code. Dermatopathology archives were then searched for any corresponding biopsies consistent with dermatomyositis, and those identified were assessed for eosinophils, adnexal involvement, epidermal atrophy, dermal mucin, and basement membrane thickening. Histopathologic findings were correlated with key clinical features, including itch. A total of 39 biopsies from 17 patients were included. Eosinophils were noted in 44% of biopsies ( n = 17) from 12 patients. Dermal mucin deposition and adnexal interface dermatitis were noted in 72% ( n = 28) and 44% ( n = 17) of biopsy specimens, respectively. Of 12 patients with eosinophils present in at least 1 biopsy specimen, 11 (92%) patients had a clinical history of pruritus of their skin lesions ( P = 0.052). Limitations of this study include retrospective design and small number of patients.